2020
DOI: 10.1177/2325967119892331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Function Improves After Subacromial Injection of Local Anesthetic in Full-Thickness Rotator Cuff Tears: A Randomized Control Trial

Abstract: Background: Rotator cuff pathology is the most common cause of shoulder pain in adults, accounting for nearly 70% of shoulder-related visits to clinicians. However, physical examination findings may be limited because of pain or patient inhibition. Purpose: To establish whether a relationship exists between pain, range of motion, and strength in patients with a full-thickness rotator cuff tear. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A single-blind, randomized controlled study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We excluded two recent studies including patients with revision repairs or nonoperative treatment. 5 , 24 Screening of the titles and abstracts of cited and citing references of included records and 18 topical records 7 , 8 , 9 , 15 , 23 , 24 , 26 , 30 , 35 , 40 , 42 , 55 , 58 , 60 , 70 , 71 , 72 , 73 did not yield any additional studies that met our inclusion criteria. A full description of included studies (studied population, outcomes, statistical analyses, and reported effect estimates) is available in Supplemental Tables 1-3 .…”
Section: Resultsmentioning
confidence: 99%
“…We excluded two recent studies including patients with revision repairs or nonoperative treatment. 5 , 24 Screening of the titles and abstracts of cited and citing references of included records and 18 topical records 7 , 8 , 9 , 15 , 23 , 24 , 26 , 30 , 35 , 40 , 42 , 55 , 58 , 60 , 70 , 71 , 72 , 73 did not yield any additional studies that met our inclusion criteria. A full description of included studies (studied population, outcomes, statistical analyses, and reported effect estimates) is available in Supplemental Tables 1-3 .…”
Section: Resultsmentioning
confidence: 99%
“…By the final follow-up, 212 patients were lost. A total of 74 of the 79 studies were single-centered [ 1 , 2 , 5 , 6 , 7 , 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Rotator cuff tear (RCT) is common in the elderly leading to loss of athletic ability and weakened strength, which has a signi cant impact on daily activities [1,2]. Generally, the clinical effect of surgical repair of rotator cuff injury is excellent.…”
Section: Introductionmentioning
confidence: 99%